A novel prototype and simulation model for real time solid waste bin monitoring system - Md. Abdulla Al Mamun; M. A. Hannan; Aini Hussain (Fakulti Kejuruteraan ,UKM,Bangi., 2014)
This research deals with an exclusive solution to monitor the solid waste bin condition on real time. The system architecture is designed using wireless sensor networks. A set of carefully chosen sensors are used to measure the status of the bins and ZigBee and GPRS are used as communication technologies. The physical architecture of the system contains three levels such as smart bins for the measurement and transmission of bin status, gateways for storing and forwarding bin data to server and control station for storing and analyzing the data. After the framework design, a simulation is performed using Castalia to ensure the feasibility and accuracy of the system. The simulation is performed for ten bins and taking ten samples from each bin where a fi ll level threshold of 15 is considered. The simulation result shows that, the proposed system would be able to automate the solid waste monitoring process that helps to optimize waste collection route.